War & peace - a themed choral concert: a comprehensive examination of the process of preparation and performance - Griggs, Nicholas E. (Kansas State University, 2013)
This document examines five choral octavos for a themed choral concert. The McPherson High School Concert Choir will present a themed choral concert, “War and Peace”, which includes these five octavos, on October 14, 2013 at 7:30pm. The selections reflect the program theme and include historical and theoretical analysis. Along with the analysis, this document also contains rehearsal plans and examines common practices of selecting and preparing literature for a themed choral concert. The choral octavos examined are: The Sword of Bunker Hill arranged by Matthew Armstrong, Lift Up Your Heads arranged by Hal H. Hopson, Down By The Riverside arranged by Rosephanye Powell, Tell My Father arranged by Andrea Ramsey, and Joshua Fit The Battle of Jericho arranged by Mark Hayes.
War and peace - a themed choral concert: a comprehensive examination of the process of preparation and performance
Keywords: Choral; Concert; Theme; War; Peace; Music (0413); Music Education (0522)